Coping strategies and behavioural changes following a genital herpes diagnosis among an urban sample of underserved Midwestern women. (March 2016) - Davis, Alissa; Roth, Alexis; Brand, Juanita Ebert; Zimet, Gregory D; Van Der Pol, Barbara
This study focused on understanding the coping strategies and related behavioural changes of women who were recently diagnosed with herpes simplex virus type 2. In particular, we were interested in how coping strategies, condom use, and acyclovir uptake evolve over time. Twenty-eight women screening positive for herpes simplex virus type 2 were recruited through a public health STD clinic and the Indianapolis Community Court. Participants completed three semi-structured interviews with a woman researcher over a six-month period. The interviews focused on coping strategies for dealing with a diagnosis, frequency of condom use, suppressive and episodic acyclovir use, and the utilisation of herpes simplex virus type 2 support groups. Interview data were analysed using content analysis to identify and interpret concepts and themes that emerged from the interviews. Women employed a variety of coping strategies following an herpes simplex virus type 2 diagnosis. Of the women, 32% reported an increase in religious activities, 20% of women reported an increase in substance use, and 56% of women reported engaging in other coping activities. A total of 80% of women reported abstaining from sex immediately following the diagnosis, but 76% of women reported engaging in sex again by the six-month interview. Condom and medication use did not increase and herpes simplex virus type 2 support groups were not utilised by participants. All participants reported engaging in at least one coping mechanism after receiving their diagnosis. A positive diagnosis did not seem to result in increased use of condoms for the majority of participants and the use of acyclovir was low overall.